Biomass-derived carbon/MgO-Al2O3 composite with superior dynamic CO2 uptake for post combustion capture application. Issue 54 (December 2021) - Pu, Qiuyun; Wang, Yi; Wang, Xiaocheng; Shao, Zhitao; Wen, Shikun; Wang, Junya; Ning, Ping; Lu, Shijian; Huang, Liang; Wang, Qiang
Highlights: A biomass-derived carbon/MgO-Al2 O3 composite with high efficiency dynamic CO2 capture performance was prepared. The effect of synthesis conditions and magnesium source of composite was studied. The CO2 uptake of composite loaded with single MgO and binary MgO-Al2 O3 was compared. The CO2 adsorption kinetics of biomass-derived carbon/MgO-Al2 O3 composite was analyzed. Abstract: In this work, the biomass-derived activated carbon (AC)/MgO-Al2 O3 composite with high-efficiency dynamic carbon dioxide (CO2 ) capture performance was prepared. The effects of MgO loading ratio, calcination temperature, calcination time, and magnesium source on the CO2 uptake of AC-based composites were studied. Moreover, the CO2 uptake of AC-based composites loaded with single metal MgO and loaded with bimetal MgO-Al2 O3 were compared, and the cyclic stability of AC-based composites under different desorption temperatures was compared. In addition, the pseudo-first-order (PFO) and pseudo-second-order (PSO) kinetic fitting analysis of the CO2 uptake at different adsorption temperatures were carried out. Finally, the AC-based composites were thoroughly characterized by BET, SEM, EDX, FT-IR and XRD. The most optimal AC-based composite with bimetal MgO-Al2 O3 shows the maximum dynamic CO2 uptake of 4.50 mmol g -1, which is comparable to the static CO2 capture performance in the previous report. It suggested that biomass-derived carbon/MgO-Al2 O3 composite has high potential application value in the development of CO2 adsorption materials.